2004
DOI: 10.1007/s11239-005-0348-3
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancies and Oral Contraceptive Therapy in Severe (Homozygons) FXII Deficiency: A Study in 12 Patients and Review of the Literature

Abstract: Twelve women with severe Factor XII (FXII) deficiency were under observation for an average period of about 16 years. During this time, these women had 19 pregnancies without any bleeding or thrombotic complications. The evaluation of the literature has shown that three patients manifested deep vein thrombosis during pregnancy. Five women also showed mild bleeding at delivery . The significance of these findings is not clear since thrombotic and bleeding complications may occur occasionally even in normal wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The data supplied by the authors in favour of a prothrombotic role of FXII deficiency have not been confirmed with the only possible but still open, exception for DVT in patients with severe FXII deficiency occurring during pregnancy [11].…”
Section: Dear Sirmentioning
confidence: 83%
“…The data supplied by the authors in favour of a prothrombotic role of FXII deficiency have not been confirmed with the only possible but still open, exception for DVT in patients with severe FXII deficiency occurring during pregnancy [11].…”
Section: Dear Sirmentioning
confidence: 83%
“…Although it has been argued that formation of microthrombi may be the pathway through which factor XII deficiency could cause miscarriage, 35 it is not yet clear whether this condition actually predisposes to thrombosis, 38,39 and both deep venous thrombosis and mild postpartum hemorrhage have been reported in a small series of pregnant women with factor XII deficiency. 40 Abnormal invasion is also a potential mechanism for miscarriage in thrombophilic disorders, but there are no studies on the effect of factor XII deficiency in placental invasiveness.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, in our article we defined this correlation at least doubtful because of the contradictory aspects emerging from the literature data, with some studies in which it is considered inexistent [3][4][5][6], except for some conditions, as correctly pointed out in the explanatory letter [7]. Nevertheless, the matter presents interesting aspects that steel need to be elucidated.…”
Section: Dear Sirmentioning
confidence: 88%